Buckling collapse study for the carcass layer of flexible pipes using a strain energy equivalence method. (1st January 2016) - Tang, Minggang; Lu, Qingzhen; Yan, Jun; Yue, Qianjin
Abstract: When a flexible pipe is subjected to high external hydraulic pressure, the innermost carcass layer serves to resist buckling and collapse. The maximum external pressure that the carcass layer can withstand before buckling collapse must be considered during pipe design. To study this problem, a strain energy equivalence method is proposed to transform a representative volume element (RVE) of the carcass layer, which has a complex geometry, into a homogeneous shell with an equivalent thickness. To obtain the strain energy, a finite element model of the RVE is developed, and the analytical equations for the homogeneous shell are derived for the same uniform-strain boundary conditions. Radial compression tests on three different carcass layer test pieces are performed to verify the safety and effectiveness of the proposed equivalence method. The strain energy equivalence method is found to give conservative results when compared to other equivalence approaches. The advantages of the method for designing a collapse-resistant carcass layer in engineering practice are also discussed. Highlights: We investigate the buckling collapse of the carcass layer of flexible pipes. We develop a strain energy equivalent method to estimate the critical pressure. We performed the radial compression tests on 3 different carcass layer test pieces. The method proposed is proved to be safe and efficient.